A modified θ projection model for constant load creep curves-II. Application of creep life prediction. Issue 4 (April 2019) - Fu, Chao; Chen, Yadong; Yuan, Xiaofei; Tin, Sammy; Antonov, Stoichko; Yagi, Koichi; Feng, Qiang
Abstract: To minimize the deviation of the predicted creep curves obtained under constant load conditions by the original θ projection model, a new modified version that can be expressed by ε = θ 1 1 - e - θ 2 t + θ 3 e θ 4 e θ 5 ε t - 1, was derived and experimentally validated in our last study. In the present study, the predictive capability of the modified θ projection model was investigated by comparing the simulated and experimentally determined creep curves of K465 and DZ125 superalloys over a range of temperatures and stresses. Furthermore, the linear relationship between creep temperature and initial stress was extended to the 5-parameter model. The results indicated that the modified model could be used as a creep life prediction method, as it described the creep curve shape and resulted in predictions that fall within a specified error interval. Meanwhile, this modified model provides a more accurate way of describing creep curves under constant load conditions. The limitations and future direction of the modified model were also discussed. In addition, this modified θ projection model shows great potential for the evaluation and assessment of the service safety of structural materials used in components governed by creep deformation.